Articulating the supervisory functions of university supervisors in vocational education and training teaching internship - Dionne, Lucie; Gagnon, Claudia; Petit, Matthieu (Frontiers in Education, 2024)
This article examines supervisory practices in vocational education and training teaching internships within a blended-learning system. Using a multiple-case study of five triads made up of a university supervisor, a cooperative teacher from the workplace and a student teacher, practices were analysed through the lens of supervisory functions: support, mediation between theory and practice, collaboration, evaluation and internship management. Findings show that support and evaluation practices are dominant within triads. The management function is characterized by practices surrounding the selection and use of digital tools to supervise student teachers in a blended-learning system. The collaboration function appears to be inconsistent from one triad to another, while the mediation between theory and practice function plays a limited role in the practices of all supervisors, despite being identified as one of their main responsibilities.